Finding your mate in a seabird colony: contrasting strategies of the Guillemot Uria aalge and King Penguin Aptenodytes patagonicus - Lengagne, T; Harris, M P; Wanless, S; Slater, P J B (2004)
Capsule King Penguins recognize their mates by voice, but Guillemots do not need acoustic cues even though their calls show individual variation. Aims To determine whether the structure of Guillemot calls could allow individual recognition, as with King Penguin, and whether acoustic cues are used to locate mates among a dense mass of conspecifics at a colony. Methods Observations were made on breeding Guillemots and King Penguins. Calls made by birds returning to their mates were recorded, the signals digitized and the calls analysed. Calls were later played back to the mates of the birds concerned and the effects noted on both them and their neighbours. Results Both Guillemots. and King Penguins emitted calls on return to the breeding site which contained individual signatures and were therefore potentially usable for mate recognition. In King Penguins, auditory recognition was essential for finding a mate, whereas in Guillemots most of the arriving birds located their mate in a dense crowd of conspecifics without the help of acoustic signals. Guillemots could differentiate neighbours from strangers without auditory cues. Conclusion Calls are essential for the successful identification of mates by King Penguins but not by Guillemots.